Assessment of the biological pathways targeted by isocyanate using N-succinimidyl N-methylcarbamate in budding yeast Saccharomyces cerevisiae. - Gajendra Kumar Azad; Vikash Singh; Raghuvir S Tomar (PLoS ONE, 2014)
Isocyanates, a group of low molecular weight aromatic and aliphatic compounds possesses the functional isocyanate group. They are highly toxic in nature hence; we used N-succinimidyl N-methylcarbamate (NSNM), a surrogate chemical containing a functional isocyanate group to understand the mode of action of this class of compounds. We employed budding yeast Saccharomyces cerevisiae as a model organism to study the pathways targeted by NSNM. Our screening with yeast mutants revealed that it affects chromatin, DNA damage response, protein-ubiquitylation and chaperones, oxidative stress, TOR pathway and DNA repair processes. We also show that NSNM acts as an epigenetic modifier as its treatment causes reduction in global histone acetylation and formation of histone adducts. Cells treated with NSNM exhibited increase in mitochondrial membrane potential as well as intracellular ROS levels and the effects were rescued by addition of reduced glutathione to the medium. We also report that deletion of SOD1 and SOD2, the superoxide dismutase in Saccharomyces cerevisiae displayed hypersensitivity to NSNM. Furthermore, NSNM treatment causes rapid depletion of total glutathione and reduced glutathione. We also demonstrated that NSNM induces degradation of Sml1, a ribonucleotide reductase inhibitor involved in regulating dNTPs production. In summary, we define the various biological pathways targeted by isocyanates.